The fun habit : how the pursuit of joy and wonder can change your life - Rucker, Michael (Atria Books, 2023)
"The more we seek happiness, the more elusive it becomes. The Fun Habit shows readers that fun, unlike happiness, is an action you can take almost anywhere, anytime. Fun is connected to behavior and habits rather than goals, which means it's possible to get more fun into your life with intention. Whether you're a frustrated happiness-seeker looking for a new approach, a success-oriented hustler trying to balance work with a fulfilling life, or someone who experienced a life-changing trauma and needs to regain their well-being with the best medicine available, this book will show you how to reap the serious benefits fun offers us all. Grounded in science, empirical evidence, and practical recommendations, The Fun Habit delineates why you should be having more fun and shows you how to rebuild the necessary skill set you need to make fun a habit. From teaching you how to escape the happiness trap, to finding just the right kind of fun for you, to spreading the fun to your friends and family, Rucker will inspire you to incorporate a bias toward fun into every aspect of your life"--